The World Trade Organization at a crossroad: Agricultural negotiations and what it means for developing countries - Krisitina Mensah (University of Bonn, Center for Development Research (ZEF), 2024)
The World Trade Organization (WTO) serves as a key forum for negotiating global trade rules, yet it faces significant challenges, particularly in the agricultural negotiations. The collapse of the Doha Round has left critical agricultural issues unresolved. Additionally, the WTO's dispute settlement system has been weakened, undermining the enforcement of its rules and further complicating efforts to resolve agricultural disputes. The standstill of agricultural negotiations has led to concerns about the role of developing countries in world trade and how the WTO can serve their interests. This essay examines the structural limitations within the WTO's agricultural negotiations and explores how developing countries can better navigate these complex discussions. By analyzing the legacy of the Agreement on Agriculture (AoA), the role of emerging economies, and recent shifts in global trade dynamics, the essay outlines strategic approaches and identifies opportunities of the EU and Germany for revitalizing agricultural negotiations and the dispute settlement mechanism.
Keywords: F13; O19; Q17; Q18; 330; WTO; Doha round; agricultural negotiations; public stockholding; dispute settlement; trade policy